Leadership characteristics and digital transformation - Porfírio, José António (2021)
Digital transformation (DT) is essential for all companies and industries, depending crucially on systems, IT, strategy, and people. In this research, we analyse how firms’ characteristics, associated with management characteristics, promote DT in Portuguese companies. The model considers the relationship between digital strategy and corporate and business strategy, according to firm and management characteristics. We use a multilevel analysis, applying fsQCA to data obtained from 47 Portuguese firms. The results represent an important step forward in the knowledge of the conditions to promote higher stages of DT, especially regarding leadership and management associated with certain firms’ characteristics. The conclusions support the crucial role of leadership and especially the importance of managers’ coherence towards companies’ mission to promote more advanced stages of DT. At the same time, it contributes to develop knowledge about the best possible combination of firms’ and management characteristics to promote DT.